POLICY IMPLEMENTATION IN FLOOD MITIGATION (CASE STUDY IN TANJUNG UNGGAT, BUKIT BERSTARI SUB-DISTRICT, TANJUNGPINANG CITY) - Juliandi, Aditya; Matthew Pardede, Benyamin; Saputra, Aidil (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Floods are a disaster that we often hear about in Indonesia and one of them is in Bukit Bestari District because that area often experiences flooding. The flood occurred due to rainfall. In addition, the residential area is close to the river. Therefore, the government needs to provide mitigation for these residential areas. This study uses a qualitative descriptive approach that tries to describe a situation based on known facts. Data were collected through observation, in-depth interviews and documentation, and the data sources were primary data and secondary data. From the results of this study, it will answer the formulation of the research problem that the efforts of the Tanjungpinang city government in implementing policies in flood mitigation are seen from rainfall, watersheds, slum areas, and waste generation in residential areas in the Tanjung Unggat area, so that attention is needed serious from the government. Therefore the suggestion from researchers is the need for an increase in water catchment areas or the relocation of slum areas in Tanjung Unggat.